Philosophical Inquiry as a method for teaching Islamic Education - Wan Yusoff, Wan Mazwati; Juperi, Juhasni Adila; Preece, Abdul Shakour Duncan (Routledge, 2022)
Teaching methods used for teaching Islamic education are generally still very traditional and teacher-centred, which greatly influences students’ interest in learning. This has created a gap between the learners, Islamic knowledge and moral behaviour. This chapter presents community of philosophical inquiry (COPI) as a method for teaching Islamic studies, which not only stimulates students’ critical, creative and caring thinking but also promotes positive other outcomes such as collaboration, verbal communication, engagement and self-confidence. Moreover, COPI promotes Islamic studies teachers’ professional development by enhancing their thinking skills and making them better role models in the classroom. This chapter will elucidate the meaning and process of COPI, as well as present sample lesson plans for applying COPI in the Islamic studies classroom.